Head morphology in three species of tiger beetles (Coleoptera: cicindelidae): a geometric morphometric study - Y. Koçak; A. Doğan Sarikaya; Ö. Sarikaya; R. Macirella; F. Talarico; E. Brunelli (The European Zoological Journal)
Tiger beetles are one of the world’s most studied groups of insects. They are similar in body shape and proportions and have a well-sclerotized head with large protruding eyes that make it wider than the pronotum. Despite body shape being a fundamental metric of animal diversity, the current state of detailed data on tiger beetles’ external morphology needs to be improved. Geometric morphometrics is increasingly used in entomology, representing a powerful tool to capture subtle differences that can aid in taxonomic decisions. Broad literature data provide evidence for the effectiveness of geometric morphometrics in quantifying the differences in size and shape between the sexes in coleopteran species. In contrast, most of the available morphological studies on tiger beetles rely on traditional morphometrics. Here, we examined and compared the head morphology in three species of tiger beetles belonging to the genus Calomera, widely distributed in Turkey, using geometric morphometrics to reveal putative intra- and interspecific differences. While there remain many gaps in our understanding of the processes that contribute to shape differences in closely related species, our study is the first to demonstrate the existence of variations in head shape and size in Anatolian tiger beetles using geometric morphometrics. Additionally, our findings revealed significant differences in shape and size across all three studied species, also showing that head size significantly differs between males and females. This study aims to contribute to the discussion on interspecific and intersexual differences in cicindelids by proposing a methodological approach that could represent a valuable investigative tool.